Eco efficiency of Integrated Soil Fertility Management in Western Kenya - Sommer, Rolf; Mukalama, J; Kihara, Job Maguta; Koala, Saidou; Bossio, Deborah A.; Winowiecki, D (2014)
Eco efficiency of Integrated Soil Fertility Management in Western Kenya Sommer et al 2014 presented at 20th World Congress of Soil Science